Geography and the Anthropocene - Gonencgil, Barbaros; Meadows, Michael E. (Istanbul University Press, 2024)
We frequently use the terms 'developing world' and 'developing countries' and today, with a human population that now exceeds 8 billion, there is a tendency to measure development purely in the context of our own welfare. However, development and economic growth are inseparable from the resources provided by the environment, where these are utilized unsustainably - as it appears is increasingly the case - future generations will be unable to survive at all, and 'development' will be irrelevant. According to some authors after the Industrial Revolution, some after the Second World War, and others from the beginning of the 2000s, humankind has entered a period in which human activities dominate the environment. This is the so-called "Anthropocene Age", which may arguably have commenced as early as the mid-Holocene with the Agricultural Revolution. Whatever the case, and whenever the beginning, today we are witnessing a seemingly reckless struggle by humans to dominate the global environment. Unfortunately, without intervention, the end of this process may be chaos. Pollution and degradation, manifested especially in anthropogenic climate change, remind us starkly that we face an uncertain future if we do not acknowledge and address our role in changing the global environment. Geographers have much to offer in this context, and the chapters in this volume explore various aspects of the Anthropocene from a geographical perspective. We wish to thank all our colleagues who contributed their scholarship to this volume. We acknowledge the support of Istanbul University Press and the university administration who greatly facilitated the publication of this book.